Use of music in occupational therapy dedicated to the people in their older years - Michalina Radzińska; Marta Podhorecka; Walery Zukow; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2018)
Music accompany us since our childhood. We can use it to create our mood, regulate tension or to become well-disposed towards doing certain actions. Richness of musical world has been used therapeutically for ages, regardless of geographical location, and benefits connected with it have universal value. This article aims to display some possible uses of music, as a factor supporting occupational therapy dedicated to people in their older years. According to ongoing demographic changes and aging of human population, needs of this group are respected by growing throng of specialists responsible for holistic approach to treatment.